Synergistic inhibition of Aspergillus flavus by organic acid salts: growth, oxidative stress, and aflatoxin gene modulation - Yu, Yingying; Li, Fengming; Cheng, Zhiqiang; Li, Mengfei; Xu, Zihao; Sun, Long; Zang, Changjiang; Li, Xiaobin; Yang, Kailun (Frontiers in Veterinary Science, 2025)
Fungal contamination represents a critical challenge in feed production. To address this issue, organic acids and their salts are widely employed as mould-inhibiting additives. Compared to traditional organic acids, their salt derivatives offer superior stability and lower corrosivity. This study conducted an in vitro investigation to evaluate the effects of three organic acid salts, when used in combination, on the mycelial growth, cellular integrity, antioxidant status, and toxigenic gene expression of Aspergillus flavus (A. flavus). The results demonstrated that a composite organic acid salt of sodium diacetate, sodium dehydroacetate, and sodium benzoate (2:1:1 ratio) exerted optimal antifungal efficacy. Treatment with this composite organic acid salt effectively inhibited mycelial growth and resulted in a substantial decrease in mycelial dry weight. It also compromised cellular integrity, evidenced by a concentration-dependent increase in extracellular relative conductivity and a concurrent reduction in pH. Furthermore, the composite organic acid salt potently suppressed the biosynthesis of total lipids and trehalose but had no significant effect on the ergosterol mass fraction. The composite organic acid salt also induced oxidative stress, characterized by an increase in superoxide dismutase and glutathione peroxidase activities, suppression of catalase activity, and a significant accumulation of malondialdehyde. Compared to the control group, the MIC group of the composite organic acid salt significantly reduced the relative expression levels of genes encoding the aflatoxin synthesis pathway, including aflR, aflS, aflC, aflD, aflT, and aflM genes. In conclusion, the composite organic acid salt exhibits a multi-target, synergistic mechanism against A. flavus by inhibiting mycelial growth, disrupting cellular structure, inducing oxidative damage, and suppressing toxigenic gene expression. Its effectiveness, particularly at the MIC, highlights its considerable potential as a feed preservative.